Respuesta :

Answer:

The answer to your question is:    (x + 2)(3x - 1) = 0

x1 = -2

x2 = 1/3

Step-by-step explanation:

                                           3x² + 5x − 2 = 0

Multiply 3 x -2 = -6

Find two numbers that added = +5 and multiply -6

These numbers are +6  and -1

Then:

                                           3x² + 6x -1x − 2 = 0

Factorize                           3x (x + 2) - 1(x + 2) = 0

Factorize again                (x + 2)(3x - 1) = 0

Finally

                         x + 2 = 0               3x - 1 = 0

                         x = -2                     x = 1/3